Periodismo actual: notable en tecnología, aprobado muy justo en calidad - López García, Xosé (Estudios sobre el Mensaje Periodístico, 2002)
Nowadays, the changes that operate in the hypersector of communications are so fast, that is difficult to foresee the consequences they can exert in journalism. We face a very complex phenomenon. It is not a matter of doubt that the number of researchers, work lines and also groups concerned with future tendencies is increasing. Even though, they are not combined factors ready to overcome the challenges we are facing. The cause is that we do not give answers to the questions, which are raising and multiplying from time to time. The aim of this paper is to analize the impact of technological modernization made to improve the quality of the journalistic products and journalism in general. We use for that purpose a case study: Galician press let us observe some symptoms of the way we have been following during the last 25 years in something we still call journalism. This is the first part of a research project that is currently working on. It will be concluded in a couple of years with the monitoring and textual and formal analysis of the Galician newspapers.
Keywords: Press; Journalism; Information contents; Information Technology